CHECKLIST ON FAUNA DIVERSITY GUNUNG HALIMUN SALAK NATIONAL PARK: Cikaniki-Citalahab - Agmal Qodri; Ilham Vemandra Utama; Pamungkas Rizki Ferdian; Endah Dwijayanti; Rusdianto Rusdianto; Yohanna Yohanna; Mulyadi Mulyadi; Nanang Supriatna; Rena Tri Hernawati; Fajrin Shidiq; Encilia Encilia; Gloria Animalesto; Pangda Sopha Sushadi; Anang Setyo Budi; Syaiful Rizal; Ujang Nurhaman; Alamsyah Elang Nusa Herlambang; Ayu Savitri Nurinsiyah (ZOO INDONESIA, 2020)
The Cikaniki resort is one of the most accessible research stations located in the Gunung Halimun Salak National Park (GHSNP). It is in adjacent with Citalahab village. The Research Center for Biology, Indonesian Institute of Sciences and other institutions have conducted intensive research on the fauna diversity of GHSNP from this station. Here we formulate a checklist on fauna diversity surrounding the Cikaniki Research Station and Citalahab, GHNSP from various sources, i.e. field work, museum collections (Museum Zoologicum Bogoriense), scientific publications, and technical report. The study was conducted from October 2019 until October 2020. The latest field work was conducted from 8-10 October 2019 under the framework of the Jungle Survival and Biological Collection Management 2019 program. In total, 821 fauna species were recorded in Cikaniki-Citalahab areas which comprises of 48 species of Mollusca, five species of Malacostraca, 523 species of Insects, 22 species of Actinopterygii, 63 species of Amphibia and Reptiles, 115 species of Aves and 45 species of Mammals. The diversity contributes 62.1% of the total 1,323 known fauna species in GHSNP. Five number of species were assigned as endangered and three species critical endangered by IUCN. In addition, 123 species were endemic to Java and 34 species protected by Regulation of the Ministry of Environment and Forestry Republic of Indonesia Number P.106/MENLHK/SETJEN/KUM.1/12/2018. The areas of Cikaniki and Citalahab are rich in biodiversity. Although both areas are in close intact with human activity, research and ecotourism, the need of continuously spreading awareness and enforce species and area conservation is inevitable.